Rasulullaah Sebagai Role Model Bagi Pendidik (Kajian Terhadap Al-Qur’an Surah Al-Ahzab Ayat 21) - Huda, Shofiah Nurul; Afrina, Fira (Prodi PAI STAI Sumatera Medan, 2020)
Moral decadence that occurs in the modern era does not only occur in students, but also in educators. educators should be role models in morals. In Islam, there is the best model that is used as a human role model in all aspects, namely the Prophet Muhammad, in accordance with the sound verse in the QS. Al Ahzab verse 21 which if examined turns out to have implied the personality of the Prophet that can be imitated in it, then this study will focus on finding solutions by making the Prophet as a role model for educators. So the main purpose of writing this journal is to get an explanation that the Messenger of Allah is indeed a role model for educators and how the specifications of the character of the Prophet as a role model for educators who are studied based on the interpretation of QS Al-Ahzab paragraph 21. The assessment is carried out using the library research method with content analizing technique from the interpretation of Surah Al-Ahzab verse 21. This study produces an explanation of the truth of the Prophet as a role model for educators and a description of the Prophet's personality specifications as a role model for educators based on the interpretation of QS Al-Ahzab verse 21 which is a solution to the moral crisis for educators in Indonesia.